A Numerical Study on the Formation and Maintenance of a Long‐Lived Rainband in Typhoon Longwang (2005). Issue 19 (15th October 2019) - Li, Yuanlong; Lin, Yanluan; Wang, Yuqing
Abstract: A 14‐hr long‐lasting spiral rainband of landfalling Typhoon Longwang (2005) was investigated based on a high‐resolution simulation using the Advanced Research version of the Weather Research and Forecasting model. This rainband was previously suggested to be triggered and maintained by vortex‐Rossby wave (VRW) dynamics based on available observations. The simulation results in the present study further suggest that the rainband originated from a previously existing wavenumber‐2 VRW. The wave amplified via a positive feedback between Ekman pumping and diabatic heating. The wavenumber‐1 convective forcing induced by the deep‐layer environmental vertical wind shear also contributed to the amplification of the rainband after its formation. Although both observations and simulation showed the long‐lived (greater than 10 hr) rainband with leading stratiform precipitation, unlike in observations, the rainband in the simulation showed a transition from an inner rainband to an outer rainband when the simulated rainband moved beyond the VRW stagnation radius at about 140 km from the storm center. As a result, in the band's later stages, VRW dynamics could not contribute to the maintenance of the rainband. Instead, both cold‐pool dynamics and vertical wind shear‐induced wavenumber‐1 convective forcing played key roles in the further maintenance of the rainband. Key Points: A long‐lived rainband (14 hr) in Typhoon Longwang (2005) was studied using a high‐resolution numerical simulation The rainband was triggered by a wavenumber‐2 vortex Rossby wave and further intensified by vertical wind shear‐induced wavenumber‐1 forcing The rainband showed a transition from a vortex Rossby wave‐dominant inner rainband to a cold‐pool dynamics‐dominant outer rainband